2022
DOI: 10.3390/molecules27041240
|View full text |Cite
|
Sign up to set email alerts
|

Deeper Insight into the Volatile Profile of Rosa willmottiae with Headspace Solid-Phase Microextraction and GC–MS Analysis

Abstract: As the distribution center of Rosa in the world, China has abundant wild germplasm resources, which can contribute to the breeding of modern roses. To explore the potential value of wild roses distributed in the Sichuan–Tibet region, solid phase microextraction (SPME) and gas chromatography–mass spectrometry (GC–MS) were used to determine the volatile organic compounds (VOCs) in Rosa willmottiae flowers at three flowering stages (bud stage, initial flowering stage, full flowering stage). Meanwhile, we compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the same genus, different aromatic species or cultivars possesses common or different VOCs. The common VOC categories of flowers (i.e., terpenes, alcohols, and esters) have been reported in Cymbidium faber (Omata et al 1990), Dendrobium (Yang et al 2022), and Rosa (Jiao et al 2022) and were also detected in the native species Phal. violacea (Chuang et al 2017), Phal.…”
Section: Discussionmentioning
confidence: 77%
“…In the same genus, different aromatic species or cultivars possesses common or different VOCs. The common VOC categories of flowers (i.e., terpenes, alcohols, and esters) have been reported in Cymbidium faber (Omata et al 1990), Dendrobium (Yang et al 2022), and Rosa (Jiao et al 2022) and were also detected in the native species Phal. violacea (Chuang et al 2017), Phal.…”
Section: Discussionmentioning
confidence: 77%
“…Floral volatile profiles vary across different plants and across different growth stages [ 28 ]. Such variation depends not only on the physiological levels of plants, but also on their growth and reproduction strategies [ 29 ]. Our results indicated that the opening of L. caudata flowers was closely related to the emission of volatile compounds, resulting in a diurnal pattern in scent emission.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of plants own distinctive odors. Analyzing these odors is expected to reveal unique biomarkers for species identification and provide important data for economic valuation. HS-SPME is an excellent candidate for odor enrichment, and the mixed fibers including DVB/CAR/PDMS, CAR/PDMS, and PDMS/DVB are preferred due to the synergetic effects of absorbents and adsorbents. It is worth mentioning that the hybrid composites of silica aerogel, preyssler-type polyoxometalate, and MIL-101­(Cr) have been fabricated as a highly porous fiber coating, which has been successfully used for the headspace extraction and identification of Ferulago angulata volatile components. Exerting a magnetic field on the prepared SPME fiber using a permanent magnet substantially improves the extraction efficiency for the volatile components, to an average of 73% …”
Section: Spme In Biological Analysismentioning
confidence: 99%